OHP-080 Use of Chemotherapy Near the End of Life. (12th March 2013) - Martín, A; Ibañez, S; Blázquez, C; Muñoz, BM; Franco, MT; Fernández, AI; Rodriguez, M; Pérez, R; Encinas, C
Abstract : Background: Appropriately timed cessation of chemotherapy is integral to the patient's quality of life. Purpose: To describe and evaluate the use of chemotherapy in cancer patients in their last days of life. Materials and Methods: Retrospective observational study that included all cancer patients who died in our hospital in 2011. Information sources used were: a) Mambrino for the age, date of death of the patient and clinical charts; b) Oncofar to record the type of cancer, the last cycle of intravenous (IV) chemotherapy received, the historic administration, lines of treatment and the percentage of the last dose received; c) APD-Athos to review data from the patient's hospital stay and outpatient oral cytostatics dispensing. We collected for each patient their demographics, pharmacotherapy, the temporal interval between the last chemotherapy administration and death of the patient and the number of days in hospital one month before death. Results: A total of 94 patients (30% female) died in 2011 in our hospital. Of these, 10 patients didn't receive chemotherapy, 10 received IV chemotherapy combined with oral, 4 received oral chemotherapy alone and 70 IV chemotherapy alone. Tumours with the highest number of deaths were non-small cell lung cancer (21), head and neck cancer (11) and colorectal cancer (10). The most common last chemotherapy regimens were combinations of carboplatin (16) (especially with pemetrexed and paclitaxel), gemcitabine (11) (mostly alone), combinations of cisplatin (9), paclitaxel (9) (alone or combined with carboplatin) and monoclonal antibodies (9) (in 67% combined with bevacizumab); the most frequent oral chemotherapy drugs were erlotinib (4) and temozolomide (3). Of the 80 patients who received IV chemotherapy, 27.5% (22) received chemotherapy in the last 14 days of life, another 27.5% (22) received chemotherapy between 15 and 30 days before death, 21.25% (17) between 31 and 60 days, 13.75% (11) between 61 and 90 days and 10% (8) more than 90 days before death. In addition, 14% (12) started a new IV chemotherapy regimen a month before death. About lines of treatment, 45.25% (38) of the patients received first-line chemotherapy, 20.25% (17) in second line, 21.4% (18) in third line and 13.1% (11) received more than 3 lines of chemotherapy. In 48.75% (39), the percentage of the last dose of IV chemotherapy administered was ≤ 80%. All patients were admitted to the Oncology floor at some point in the last 30 days of life, with an average stay of 9.73 days. Conclusions: The percentage of patients receiving IV chemotherapy in the last 14 days of life and that of those who started with a new regimen a month before death are much higher in our hospital than in similar studies. In view of the results obtained, more than half of these patients received IV chemotherapy in the last month of life. This makes us ask ourselves what factors contributed to this decision to treat, were the benefit and toxicity correctly assessed and was it is really necessary to have active cancer treatment in the last days of life? No conflict of interest.